ʿAbd al-Karīm al-Jīlī, Waḥdat al-Wujūd, and Reconfiguring Epistemology - Rüdiger Lohlker (Universitas Islam Negeri Mataram, 2019)
This study introduces some new ideas into the study of ideas in Sufism. Taking al-Jīlī and, esp., his al-Insān al-kāmil as a starting point this study argues a holistic worldview following the concepts of the oneness of being (waḥdat al-wujūd) will be able to integrate – and to be integrated – into contemporary scientific concepts like chemical fluctuation, the new synthesis, and holobionts. This will lead to creating a general philosophy of being beyond the Western biases.